Characterization of Biodiesel Produced from Palm Oil via Base Catalyzed Transesterification - Ali, Eman N.; Tay, Cadence Isis (Elsevier, 2013)
Biodiesel is a notable alternative to the widely used petroleum-derived diesel fuel since it can be generated by domestic natural resources such as palm oil, soybeans, rapeseeds, coconuts and even recycled cooking oil. Interest in biodiesel has been expanding recently due to government incentives and high petroleum prices. The majority of biodiesel today is produced via base catalyzed transesterification with methanol. The crude palm oil is the raw material for this study In order to find the optimum values of biodiesel (Palm oil Methyl Ester, POME) yield, three parameters were studied: reaction temperature, reaction time and the methoxide:oil ratio. In this study, the parameters were: reaction temperature: 40, 50, and 60 °C; reaction time: 40, 60 and 80 minutes; and methoxide:oil ratio: 4:1, 6:1 and 8:1. The results showed that the optimum reaction time was 60 minutes, reaction temperature was 60 °C and the methoxide:oil ratio was 6:1, were the optimum yield of 88% was achieved. Testing and analysis was carried out to determine the physical properties of the product. The density of POME is 876.0 kg/m3, kinematic viscosity of 4.76 mm2/s, cetane number of 62.8, flash point of 170 °C, cloud point of 13 °C, pour point of 17 °C, and saponification value of 206.95 mg/L. The produced biodiesel has similar properties of ASTM D 6751, and EN 14214.